Feasibility and parameter optimization of ground-to-satellite uplink continuous-variable quantum key distribution - Jin Cheng; Yujie Chen; Ao Liu; Xin Sun; Junjie Guo; Bohan Yang; Peng Yin; Wenbo Liu; Lanjian Chen; Chen Dong (New Journal of Physics)
Driven by the necessitates of wide-area quantum secure communication networks, ground-to-satellite quantum key distribution (QKD) has been highlighted in the field of quantum information. Continuous variable QKD (CV-QKD) shows the advantages of a high secure key rate generation and compatibility in the fiber channel, but the communication range is limited by low attenuation tolerance. In this study, the feasibility of the uplink CV-QKD for Very Low Earth Orbit satellite is studied, and the influence of practical factors such as atmospheric turbulence and beam pointing errors under dynamic time-varying satellite orbital parameters is analyzed to model realistic transmission channels. A parameter optimization scheme for orbital parameters, spot size, receiving telescope aperture, and modulation variance has been proposed to enhance the performance of the actual uplink CV-QKD, providing a reference for parameter selection in CV-QKD experiments.